’n Christosentriese benadering van die gereformeerde leer as uitgangspunt van die sending - Verster, P (Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
A Christosentric approach of the reformed doctrine as the foundation of mission There can be no doubt that the holy love of God in Jesus Christ is central to the reformed doctrine. The kingdom of God should be viewed from the perspective of Christ as central to the reign of God. It is essential to base Christosentric reformed mission in the love of God. This means that the solae of reformed doctrine as well as the solus Christus, should be viewed from the perspective of the proclamation that Christ, the Son of God as God who became human, is the essence and centre of the reformed doctrine. Therefore, it is impossible to reject the powerful missionary commission of the Gospel or to view mission only from the perspective of service.